1986
DOI: 10.3402/tellusb.v38i5.15139
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of mechanically generated turbulence and interfacial films with a liquid phase controlled gaslliquid transport process

Abstract: The liquid phase rate-controlled transport of C 0 2 across a gas/liquid interface into water was studied using a non-invasive laser-induced fluorescence (LIF) technique. Turbulence in the liquid layer was generated by a vertically-oscillating grid. The CO,/water interface was cleaned by removal of surface water with additive-free lens paper, or 100% rayon cloth followed by surface vacuuming with a glass Pasteur pipette. The liquid phase mass transfer coefficient k, was measured under conditions of varying turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Natural, filtered seawater was used in the tank for all tests, and sodium hypochlorite was periodically used to control bacterial growth and contamination. Prior to the start of measurements on a given day, the water surface was cleaned of dust and surfactants through suctioning and physical wiping of the surface with lint-free optical paper [38]. A layer of saltwater foam approximately 1.7 cm thick was generated by forcing compressed laboratory air at a rate of 0.4 l s −1 that had been filtered to remove water and oil through a submerged diffuser in the tank.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Natural, filtered seawater was used in the tank for all tests, and sodium hypochlorite was periodically used to control bacterial growth and contamination. Prior to the start of measurements on a given day, the water surface was cleaned of dust and surfactants through suctioning and physical wiping of the surface with lint-free optical paper [38]. A layer of saltwater foam approximately 1.7 cm thick was generated by forcing compressed laboratory air at a rate of 0.4 l s −1 that had been filtered to remove water and oil through a submerged diffuser in the tank.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Table 2 summarizes the experimental conditions. A salinity range of 2-40 psu was chosen to span values observed from lakes to estuaries to the open ocean. Salinity differences were achieved using laboratory-grade sodium chloride (NaCl) without additional cleaning procedures [21]. The salinity of the water was varied in steps of δS ∼ = 4-6.5 psu by adding an appropriate amount of salt to the water volumes used in each experiment.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In support of Equation 2, Asher and Pankow (1986) found that for carbon dioxide (COJ scaled Iineariy with e". They also found B to be in the range 0.65 to 1.2, depending on cleanliness of the water surface.…”
Section: Equation 1 Was Derived By Assuming Thatmentioning
confidence: 88%